Has Stratospheric HCl in the Northern Hemisphere Been Increasing Since 2005? - Han, Yuanyuan; Xie, Fei; Zhang, Jiankai (Frontiers in Earth Science, 2020)
Stratospheric hydrogen chloride (HCl) is the main stratospheric reservoir of chlorine, deriving from the decomposition of chlorine-containing source gases. Its trend has been used as a metric of ozone depletion or recovery. Using the latest satellite observations, it is found that the significant increase of Northern Hemisphere stratospheric HCl during 2010–2011 can mislead the trend of HCl in recent decades. In agreement with previous studies, HCl increased from 2005 to 2011; however, when the large increase of stratospheric HCl during 2010–2011 is removed, the increasing linear trend from 2005 to 2011 becomes weak and insignificant. In addition, the linear trend of Northern Hemisphere stratospheric HCl from 2005 to 2016 is also weak and insignificant. The significant increase of HCl during 2010–2011 is attributed to a strong northern polar vortex and a weakened residual circulation, which slowed down the transport of HCl between the low–mid latitudes and the high latitudes, leading to an accumulation of HCl in the middle latitudes of the stratosphere. In addition, a weakened residual circulation leads to enhance conversion of chlorine-containing source gases of different lifetimes to HCl, thus increasing the levels of HCl. Simulations by both chemistry transport and chemistry-climate models support the result. It is further found that the joint effect of a La Niña event, the west phase of the quasi-biennial oscillation (WQBO) and positive anomalies of sea surface temperature in the North Pacific (positive SSTNP) is responsible for the strong northern polar vortex and a weakened residual circulation.